Body Fat Percentage of Male Martial Arts Athletes Preparing for PON Papua - Y. Touvan Juni Samodra; Isti Dwi Puspita Wati; Maharani Fatima Gandasari; Ghana Firsta Yosika; Putra Sastaman B; Davi Sofyan (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
The required fat percentage for martial athletes is an important component. The purpose of this study was to describe the body fat percentage of martial arts athletes from Tarung Rajat, Boxing, Kempo, Pencak Silat, Taekwondo, Kempo, and Muay Thai who were chosen as the best athletes for the Papua New Guinea PON preparation. The number of samples is 70 athletes, with details of 7 taekwondo, 13 tarung drajat, 16 pencak silat, 24 boxing, 3 kempo, and 7 muay thai. Measurements were made with the Omron Karada Scan HBF-375 balance. The data were analysed with descriptive statistics. The results showed that the overall average percentage of athletes' body fat was 15.17%, included in the normal category. And you can say that the body fat percentage of martial arts athletes in this study is in the low category.